Surface roughness model for high speed end milling of soda lime glass using carbide coated tools with compressed air blowing - Mahmud, M. A.; Amin, A. K. M. Nurul; Arif, Muammer Din (Trans Tech Publications, Switzerland, 2012)
Glass materials play a vital role in advancement of science and technology. They have found wide spread application in the industry, in laboratory equipment and in micro-gas turbines. Due to their low fracture toughness they are very difficult to machine, moreover there are the chip depositions on the machined surface which affects surface finish under ductile mode cutting conditions. In this research, high speed end milling of soda lime glass is performed on CNC vertical milling machine to investigate the effects of machining parameters i.e. spindle speed, depth of cut, and feed rate on machined surface roughness. Design of experiments was performed following Central Composite Design (CCD) of Response Surface Methodology (RSM). Design Expert Software was used for generating the empirical mathematical model for average surface roughness. The model’s validity was tested to 95% confidence level by Analysis of Variance (ANOVA). Subsequent experimental results showed that the developed mathematical model could successfully describe the performance indicators, i.e. surface roughness, within the controlled limits of the factors that were considered.